KOMPARASI EFEK PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT TERHADAP INDEKS HARGA SAHAM GABUNGAN TAHUN 2021 - Edwin Wiguna; Aulia Safira; Agus Munandar (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This article analyzes the movement of the Composite Stock Price Index (IHSG) in Indonesia during the Implementation of Restrictions on Community Activities (PPKM) in 2021. PPKM is a government regulation to deal with the Covid-19 pandemic. Before the implementation of PPKM, the government had implemented large-scale social restrictions implemented in several regions in Indonesia. The policy implemented by the government is considered to have an impact on the decline in people's purchasing power, which has just shown recovery and has an impact on several sectors of the stock market in Indonesia. It is necessary to analyze to determine the effect of implementing community activities on the joint-stock price index in 2021. This study uses an exploratory descriptive type of research. Observations were made by analyzing the composite stock price index (IHSG). Based on the results of the discussion that has been analyzed, it can be concluded that during the implementation of restrictions on community activities (PPKM) the IHSG value tends to experience a difference every month but shows a positive trend which closed at the level of 6,600.68, which was an increase of 10.4 percent compared to the 2020 closing position. which is at 5,979.07.